Synchronic and diachronic variation phenomena in inverted interrogative and related contexts in Northern Italian dialects - Chiara Polo (Nordlyd: Tromsø University Working Papers on Language & Linguistics, 2007)
In the spirit of Ferdinand de Saussure, the present contribution is offered as an integrated synchronic and diachronic analysis of syntactic variation phenomena across a selected number of Veneto and other Northern Italian dialects: the main focus of the study will be on (unembedded) interrogative clauses. The goal targeted is to account for the wide range of structural options allowed by contemporary dialects (VS/SV/SVS) in the light of the discrepant evolutionary stages they embody and reflect, as independently reconstructed and singled out in the history of the Venetian dialect. Seemingly idiosyncratic contemporary inter-dialectal variation phenomena are thus viewed as functions of the different parametric values dialects activate in dependence on the position they occupy in an evolutionary continuum which promotes the elimination of an anciently fully productive inverted pattern VS (along with the syntactic rule V-to-C which possibly underlies its generation).